2001
DOI: 10.1046/j.0333-1024.2001.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervicogenic Headache: Evaluation of the Original Diagnostic Criteria

Abstract: A variety of headaches are frequently associated with the occurrence of neck pain. The purpose of this paper was to describe the adherence to diagnostic criteria of a series of patients enrolled on the basis of two clinical criteria: (1) unilateral headache without side-shift, and (2) pain starting in the neck and spreading to the fronto-ocular area. One hundred and thirty-two patients (36 male and 96 female) entered the study. Sixty-two patients were assigned to Group A (patients fulfilling criteria 1 and 2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 24 publications
0
68
0
6
Order By: Relevance
“…The combination of pain first felt in the neck and then spreading unilaterally to the frontal area on the same side fortifies the suspicion that one may be faced with a case of CEH. The site and radiation of pain, the temporal pattern and the mechanical precipitation of attacks, both iatrogenically and subjectively, are important aspects of the clinical picture and may help in distinguishing between CEH on the one hand and migraine and TTH on the other [13,14]. In patients with bilateral pain, but still with a preponderance on the usual side, anaesthetic blockades become mandatory even in clinical practice.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…The combination of pain first felt in the neck and then spreading unilaterally to the frontal area on the same side fortifies the suspicion that one may be faced with a case of CEH. The site and radiation of pain, the temporal pattern and the mechanical precipitation of attacks, both iatrogenically and subjectively, are important aspects of the clinical picture and may help in distinguishing between CEH on the one hand and migraine and TTH on the other [13,14]. In patients with bilateral pain, but still with a preponderance on the usual side, anaesthetic blockades become mandatory even in clinical practice.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Pain, stemming from the neck, usually spreads to the oculofrontotemporal area [3,4]. It is moderate in intensity, appears more frequently in women, and is associated with signs and symptoms linking it to the neck [4,5]. Although unilaterality of pain was a strict criterion as defined in the original criteria for CH diagnosis, recent reports proposed that it might also be bilateral [3].…”
Section: Introductionmentioning
confidence: 99%
“…There are still some unresolved questions about the differential diagnosis of CH, TTH and MWOA. Although some reports indicated that anaesthetic blockade of GON is accepted as a diagnostic tool for CH, some studies showed the effectiveness in patients with TTH or MWOA [4,[7][8][9][10]. The aim of this placebo-controlled, randomised and double-blind study was to evaluate the diagnostic value of GON blockade in patients with CH, TTH and MWOA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations